2024
DOI: 10.1002/mnfr.202300586
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Impact of Probiotic‐Fermented Soymilk on Dextran‐Sulfate‐Sodium‐Induced Ulcerative Colitis via Modulating Inflammation and Gut Microbiota Profile

Philippe Madjirebaye,
Fei Peng,
Abdul Mueed
et al.

Abstract: ScopeLactic acid bacteria with probiotic functions and their fermentation products play a role in regulating ulcerative colitis (UC). This study investigates the potential role of fermented soymilk (FSM4) rich in isoflavones on DSS‐induced UC.Methods and ResultsMice received 3% DSS and are supplemented daily once for 1 week by NFSM and FSM4. DSS usually causes intestinal inflammation and alters the gut microbiota. FSM4 intervention improves the UC‐related inflammation and gut microbiota alteration. It consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Interestingly, we also found that the combination of PAC and T. muris infection led to the expansion of zOTUs corresponding to the Escherichia fergusonii which was absent in all other treatment groups ( p < 0.01 for interaction between diet and infection by two-way ANOVA; Figure 6c ). Given that the expansion of the Escherichia genus in the mouse GM is often indicative of a dysbiotic GM, 44 our data suggest that the intake of PAC together with SSD may be a risk factor for T. muris –induced dysbiosis compared to SSD consumption alone. Of note, this is consistent with some of our immunological data (e.g.…”
Section: Resultsmentioning
confidence: 72%
“…Interestingly, we also found that the combination of PAC and T. muris infection led to the expansion of zOTUs corresponding to the Escherichia fergusonii which was absent in all other treatment groups ( p < 0.01 for interaction between diet and infection by two-way ANOVA; Figure 6c ). Given that the expansion of the Escherichia genus in the mouse GM is often indicative of a dysbiotic GM, 44 our data suggest that the intake of PAC together with SSD may be a risk factor for T. muris –induced dysbiosis compared to SSD consumption alone. Of note, this is consistent with some of our immunological data (e.g.…”
Section: Resultsmentioning
confidence: 72%
“…16–18 This is consistent with our previous research, where FSM4 reduces intestinal inflammation and regulates the growth of SCFA-producing bacteria, allowing PPAR-γ activation to weaken UC stimulants. 35…”
Section: Discussionmentioning
confidence: 99%
“…These effects are often mediated through the modulation of regulatory factors like PPAR-γ, ultimately reducing the activity of the TGF-β/Smad pathway [ 105 , 111 , 124 , 125 , 136 , 147 ]. In the gut, the mechanisms remain elusive but the most consolidated evidence suggests that SCFA-producing bacteria and LAB collaborate in anti-fibrotic mechanisms through the induction of PPAR-γ [ 132 , 133 , 140 ]. Specifically, SCFA-producing bacteria can induce PPAR-γ, while LAB create a microenvironment conducive to the growth of the SCFA-producing bacteria.…”
Section: Discussion: Current Knowledge and Therapeutic Perspectives O...mentioning
confidence: 99%
“…At the intestinal level, the oral administration of L. gasseri appears to have beneficial effects on the mucosa as it stimulates the release of IgA from DCs through the activation of TGF-β [ 139 ]. The administration of fermented soymilk to a preclinical model of DSS-induced colitis showed that LAB enhanced the growth of SCFA-producing bacteria, with an increase in PPAR-γ and a subsequent reduction in the inflammatory cytokines [ 140 ]. Although there are few studies analyzing the relationship between LA and pro-fibrotic patterns at the intestinal level, we speculate that LA may protect the gut from acute inflammatory responses in part by up-regulating anti-inflammatory pathways such as TGF-β, and in part by decreasing the fibrosis mediated by this cytokine.…”
Section: Microbial Metabolites: Established Players In Intestinal Hom...mentioning
confidence: 99%